Kaplan-Meier Type Survival Curves for COVID-19: A Health Data Based Decision-Making Tool - Calabuig, J. M.; García-Raffi, L. M.; García-Valiente, A.; Sánchez-Pérez, E. A. (Frontiers in Public Health, 2021)
Countries are recording health information on the global spread of COVID-19 using different methods, sometimes changing the rules after a few days. They are all publishing the number of new individuals infected, recovered and dead, along with some supplementary data. These figures are often recorded in a non-uniform manner and do not match the standard definitions of these variables. However, using data from the first wave of the epidemic—february-june—, in this paper we show that the Kaplan-Meier curves calculated with them could provide useful information about the dynamics of the disease in different countries. We present a robust and simple model to show certain characteristics of the evolution of the dynamic process, showing that the differences of evolution among the countries is reflected in the corresponding Kaplan-Meier-type curves. We compare the curves obtained for the most affected countries so far, with the corresponding interpretation of the properties that distinguish them.